Novel sulfonated multi‐walled carbon nanotubes filled chitosan composite membrane for fuel‐cell applications. Issue 22 (8th February 2019) - Ahmed, Saad; Ali, Muhammad; Cai, Yangben; Lu, Yunhua; Ahmad, Zaheer; Khannal, Santosh; Xu, Shiai
ABSTRACT: In the present study, multi‐walled carbon nanotubes (MWCNTs) were sulfonated by 1, 3‐propane sultone and distillation–precipitation polymerization, respectively, and then incorporated into chitosan (CS) to prepare CS/MWCNTs composite membranes for fuel cell applications. CS/MWCNTs membranes show better thermal and mechanical stability than pure CS membrane due to the strong electrostatic interaction between the SO3 H groups of MWCNTs and the NH2 groups of CS, which can restrict the mobility of CS chain. The sulfonated MWCNTs provide efficient proton hopping sites (SO3 H, SO3 − ….3 + HN), thereby resulting in the formation of continuous proton conducting channels. The composite membranes with 5 wt % of MWCNTs modified by two different ways show a proton conductivity of 0.026 and 0.025 S·cm −1, respectively. In conclusion, CS/MWCNTs membrane is a promising proton exchange membrane for fuel‐cell applications. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47603. Abstract :